Keterampilan Berpikir Kreatif pada Siswa Melalui Pembelajaran Mind Mapping - Vicha, Vicha Apriana Kumalasari; Dinda, Lutfiah Adinda Nur Latifah; Zaidhah, Nabilla (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This abstract discusses research on developing creative thinking skills in students through mind mapping learning. The research approach used is quantitative with a pre-experimental research design. The research sample consisted of 30 class VIII students at a junior high school. The instruments used to collect data were creative thinking skills tests and questionnaires. Data collection techniques involve administering tests before and after treatment, as well as distributing questionnaires at the end of treatment. Data were analyzed using pre-test and post-test differences and simple statistical analysis. It is hoped that the results of this research will provide an overview of the effectiveness of mind mapping learning in developing students' creative thinking skills.